Peptide Ligands of AmiA, AliA, and AliB Proteins Determine Pneumococcal Phenotype - Nasher, Fauzy; Aguilar, Fernando; Aebi, Suzanne; Hermans, Peter W. M.; Heller, Manfred; Hathaway, Lucy J. (Frontiers in Microbiology, 2018)
The Ami-AliA/AliB oligopeptide permease of Streptococcus pneumoniae has been suggested to play a role in environmental sensing and colonization of the nasopharynx by this human bacterial pathogen by binding peptides derived from bacterial neighbours of other species in the microbiota. Here we investigated the effects of the peptide ligands of the permease’s substrate binding proteins AmiA, AliA and AliB on pneumococcal phenotype. AmiA and AliA ligands reduced pneumococcal growth, increased biofilm production and reduced capsule size. In contrast, AliB ligand increased growth and greatly increased bacterial chain length. A decrease in transformation rate was observed in response to all three peptides. Changes in protein expression were also observed, particularly those associated with metabolism and cell wall synthesis. Understanding interspecies bacterial communication and its effect on development of colonizing versus invasive phenotypes has the potential to reveal new targets to tackle and prevent pneumococcal infections.